Estimating fluxes of greenhouse gasses along the Yenisei River, Siberia, 2016 - Amon, Rainer (Arctic Data Center, 2017)
The watersheds of the large Siberian rivers store significant amounts of organic carbon in soils and vegetation. However, the lateral transport of carbon from Arctic lands to the rivers, the in-stream processing of dissolved organic carbon (DOC), and the greenhouse gas evasion from the river networks has not been well determined. During previous field work we observed a large shift in the isotopic composition of dissolved inorganic carbon (DIC), suggesting a significant in-transit loss of terrigeneous DOC. The study explored the release of greenhouse gases from the Yenisei river to the atmosphere. The hypothesis of this work is that land-based organic carbon that gets flushed into rivers does not make its way to the Arctic Ocean, where it could be deposited in the sediments. Rather, before reaching the Arctic Ocean, microbes decompose this organic carbon, resulting in a flux of carbon dioxide (CO2) and methane (CH4), both greenhouse gases, from the rivers to the atmosphere. We measured the concentration and isotopic composition of CO2 and CH4 in surface waters and air using a cavity ring down system connected to an equilibrator. Together with meteorological, radiation, high frequency temperature profile, and Acoustic Doppler Current Profiler measurements, we determined air/water gas exchange of CO2 and CH4 along the river from 56°N to 69°N.